Broadband underwater sound absorbing structure with gradient cavity shaped polyurethane composite array supported by carbon fiber honeycomb. (4th August 2020) - Wang, Zonghui; Huang, Yixing; Zhang, Xiaowei; Li, Li; Chen, Mingji; Fang, Daining
Abstract: A sound-absorbing periodically arrayed structure (SPAS) based on the combined effects of cavity resonance and impedance transition is designed. Different types of polyurethane composites are integrated to fabricate the sound-permeable layer, the gradient resonant cavity layer and the viscoelastic bottom layer. The carbon fiber honeycomb (CFH) is incorporated to the SPAS as a skeleton for better sound absorption performance under hydraulic pressure. The approximate multi-layered sound-absorption theory based on a modified transfer matrix method is adopted to predict the SPAS sound-absorption coefficient. The experimental sound-absorption coefficient of SPAS with CFH achieves 0.9 in the frequency range of 2400–10000 Hz under the hydraulic pressure of 1.5 MPa, which is promising for further practical application. The radial velocity, displacement and acoustic pressure distribution of SPAS were simulated to analyze the sound-absorption improvement in specific frequency points, showing that addition of CFH changes the sound field distribution in a positive sense.